A plasmid library of full-length zebrafish rab proteins for in vivo cell biology. Issue 1 (2nd January 2017) - Hall, Thomas E.; Martel, Nick; Lo, Harriet P.; Xiong, Zherui; Parton, Robert G.
ABSTRACT: The zebrafish is an emerging model for highly sophisticated medium-throughput experiments such as genetic and chemical screens. However, studies of entire protein families within this context are often hampered by poor genetic resources such as clone libraries. Here we describe a complete collection of 76 full-length open reading frame clones for the zebrafish rab protein family. While the mouse genome contains 60 rab genes and the human genome 63, we find that 18 zebrafish rab genes have 2, and in the case of rab38, 3 paralogues. In contrast, we were unable to identify zebrafish orthologues of the mammalian Rab2b, Rab17 or Rab29. We make this resource available through the Addgene repository to facilitate cell biologic approaches using this model.